Ageing and non-liver comorbidities in population with chronic hepatitis B infection in the western pacific region from 1990 to 2019 - Xie, Jinzhao; Wang, Xu; Pan, Deng; Liu, Jiaye; Li, Jinghua; Gu, Jing (Frontiers in Physiology, 2023)
Objectives: This study examined the age structure and burden of non-liver noncommunicable diseases (NCDs) in population with chronic hepatitis B virus (HBV) infection in the Western Pacific Region (WPR) from 1990 to 2019. Methods: We estimated ageing trends and the prevalence of non-liver NCDs among the HBV-infected population and the general population in 31 countries/areas in the WPR from 1990 to 2019 based on the Global Burden of Disease 2019 dataset. Results: The proportion of individuals aged 60 or older among the HBV-infected population has increased at a faster rate compared to the general population, whereas the proportion of individuals younger than 19 years has decreased rapidly over the past three decades. Among the HBV-infected population, the prevalence of most (29/31) NCDs increased from 1990 to 2019, with the top three most significant increases found for non-Hodgkin’s lymphoma (789.94% increase), prostate cancer (512.40% increase), and kidney cancer (411.34% increase). The prevalence of NCDs among the HBV-infected population increased faster than in the general population over the past three decades, especially in countries with rapid population ageing. Conclusions: This study highlights the increasing burden of non-liver comorbidities among the HBV-infected population. The integrated management of non-liver NCDs among this population should be implemented.